2012
DOI: 10.1186/gb-2012-13-7-r66
|View full text |Cite
|
Sign up to set email alerts
|

Genome and low-iron response of an oceanic diatom adapted to chronic iron limitation

Abstract: BackgroundBiogeochemical elemental cycling is driven by primary production of biomass via phototrophic phytoplankton growth, with 40% of marine productivity being assigned to diatoms. Phytoplankton growth is widely limited by the availability of iron, an essential component of the photosynthetic apparatus. The oceanic diatom Thalassiosira oceanica shows a remarkable tolerance to low-iron conditions and was chosen as a model for deciphering the cellular response upon shortage of this essential micronutrient.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
304
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(331 citation statements)
references
References 55 publications
23
304
3
1
Order By: Relevance
“…To refine these results, we developed a stringent classification method which, starting from the clusters of orthologous proteins, generated > 9000 phylogenetic trees containing at least one P. multistriata protein and, based on the topology of each tree, predicted 252 genes of bacterial origin specifically within diatoms. This is < 50% of the number of genes reported to be of bacterial origin in P. tricornutum (587 genes) (Bowler et al ., 2008) and more than a previous estimate at lower resolution (Lommer et al ., 2012). Repeating the analysis considering HGT events within Stramenopiles and the SAR supergroup (Stramenopiles, Alveolates and Rhizaria), we predicted 353 and 438 P. multistriata genes of potential bacterial origin, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To refine these results, we developed a stringent classification method which, starting from the clusters of orthologous proteins, generated > 9000 phylogenetic trees containing at least one P. multistriata protein and, based on the topology of each tree, predicted 252 genes of bacterial origin specifically within diatoms. This is < 50% of the number of genes reported to be of bacterial origin in P. tricornutum (587 genes) (Bowler et al ., 2008) and more than a previous estimate at lower resolution (Lommer et al ., 2012). Repeating the analysis considering HGT events within Stramenopiles and the SAR supergroup (Stramenopiles, Alveolates and Rhizaria), we predicted 353 and 438 P. multistriata genes of potential bacterial origin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The genome size, N50 value and GC content were taken from the respective publications (Armbrust et al ., 2004; Bowler et al ., 2008; Cock et al ., 2010; LĂ©vesque et al ., 2010; Lommer et al ., 2012; Tanaka et al ., 2015; Mock et al ., 2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a small percentage of proteins within each diatom belong to multi-copy gene families that commonly displayed different transcriptional patterns both within individual diatoms, as well as among the different diatoms. The extent of the genetic flexibility created by gene families may affect where and when nutrients are moved through the cell, ultimately influencing the flow of carbon and nitrogen (Lommer et al, 2012;Smith et al, 2012). For example, each diatom encodes multiple ammonium transporters, at least twice as many as the urea and nitrate transporters (Allen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that the uptake rates per unit of cell surface are similar among species with different iron requirements and as a consequence smaller cells with higher surface-to-volume ratios are favored under iron limitation (10,11). Acclimation to low iron induces rapid changes in the Photosystem (PS) II-to-PSI ratio and a global remodeling of the photosynthetic machinery (12), the down-regulation of nitrogen-reducing enzymes such as Fe-dependent nitrate and nitrite reductases, and the upregulation of enzymes involved in nitrogen recycling (13). In oceanic diatoms, metabolic adaptation to iron limitation involves a decrease of PSI and cytochrome b6/f requirements (14) and the utilization of copper-dependent plastocyanin instead of cytochrome c 6 (15,16).…”
mentioning
confidence: 99%